2017
DOI: 10.1016/j.socscimed.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Bureaucratization and medical professionals’ values: A cross-national analysis

Abstract: Understanding the impact of the bureaucratization of governance systems on the occupational values of medical professionals is a fundamental concern of the sociological research of healthcare professions. While previous studies have examined the impact of bureaucratized management, organizations, and healthcare fields on medical professionals' values, there is a lack of cross-national research on the normative impact of the bureaucratized systems of national governance. Using the European Social Survey data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
(94 reference statements)
2
17
0
2
Order By: Relevance
“…The described trend of short-term treatment also seemed to challenge the autonomy, independence and judgement of some of the professionals, as well as inducing a risk of burnout for the professionals working in the general outpatient services. This is in line with previous research, suggesting that the regulation that lies within bureaucratization and national governance weakens medical professionals' autonomy [31]. Standardization of services, such as time limitations, can lead to professionals' skepticism and resistance [7,12].…”
Section: Discussionsupporting
confidence: 90%
“…The described trend of short-term treatment also seemed to challenge the autonomy, independence and judgement of some of the professionals, as well as inducing a risk of burnout for the professionals working in the general outpatient services. This is in line with previous research, suggesting that the regulation that lies within bureaucratization and national governance weakens medical professionals' autonomy [31]. Standardization of services, such as time limitations, can lead to professionals' skepticism and resistance [7,12].…”
Section: Discussionsupporting
confidence: 90%
“…The 60-30-10 Challenge is ample warning against trudging along the same well-worn tracks to disappointment. Today's popular 'solutions' such as restructuring [38], constantly fiddling with policy settings [39], adding more and more bureaucracy [40,41], and introducing a new election manifesto or imposing fresh targets on the system every time a government changes [42] keep lots of people busy implementing 'change' but beyond superficialities; these measures conspire to constrain systems and contribute much inertia. In the end, all this top-down activity is not genuine improvement and just adds up to the same 60-30-10 gridlock.…”
Section: A Way Forwardmentioning
confidence: 99%
“…In addition to making them feel that their professional judgement and autonomy are challenged [25], they also perceive having less room for independence [6]. Research has suggested that the regulation that lies within bureaucratization and national governance weakens medical professionals' autonomy [40]. The medical profession has been described as founded on self-regulation and internally motivation, and not by external rewards [41].…”
Section: Therapist Autonomy In Mental Health Treatmentmentioning
confidence: 99%